Analysis of the Influencing Factor of Vocational Education Students Career Decisions - Ignatius Geovani Rosantono; Bernardus Sentot Wijanarka; Rihab Wit Daryono; Muhammad Nurtanto (Universitas Pendidikan Ganesha, 2021)
Career selection is a student's decision-making on the basis of understanding potential. Some of the problems of current vocational school graduates include lack of self-knowledge; not being able to decide after graduation, whether to work, study, or self-employed; lack of understanding of work; not being able to combine potential the job to be chosen; and have not been able to plan their career. The research aims to determine the effect of self-efficacy, self-concept, career maturity, vocational maturity, and career orientation of vocational students in making career decisions. The sampling technique used is probability sampling. The research subjects were students of Vocational High School grade XI and XII. The regression test data analysis techniques to determine the correlation between the independent variables and the dependent variable. The results showed that there was a positive and significant influence between career self-efficacy, self-concept, career maturity, vocational maturity, and career orientation of vocational students in career decision-making of 20.3%. Based on the research that has been done, students' career choice is the impact given to career spirit. BK and BKK are expected to be able to optimize their services related to various world information, the number of job opportunities, and qualifications needed for various professions, so that students can make independent choices